Work from home : multi-level perspectives on the new normal - Kumar, Payal, 1966-; Agrawal, Anirudh; Budhwar, Pawan S. (Bingley, U.K. : Emerald Publishing Limited, 2021)
Covid 19 was a black swan event which led to working from home emerging as the new normal at a global level. As HRM scholars we aim to understand this phenomenon from both an employee and employer perspective, while drawing on the UN's sustainable development goals (SDGs) which aspire for a fairer and more inclusive world for people and the planet. At the individual level of analysis there are chapters on conflicts between work and home life, differing levels of motivation, workplace loneliness and the work preferences of introverts and extraverts. At the organizational level questions are raised about the effects on profitability, organizational resilience, and the ability of organizations to remain innovative. How can employees be managed in terms of mentoring, role modelling and how can they be monitored for purposes of appraisal reviews? Chapters include the romanticization of WFH, a case study of shared leadership in Vienna and WFH amongst start-ups in India. In this edited book, researchers from the Global North and the Global south answer these questions, while making a seminal contribution to the field of HRM from a work from home perspective. This is an essential read not just for scholars and students of management, but also for those from the domains of psychology and sociology, and also for policy makers. This book has long-term relevance given that recent polls indicate that as a fallout of Covid-19, many employees the world over are showing a preference for a hybrid model of work - partially at the brick-and-mortar office and partially from home.
Section I: Individual Perspectives -- Chapter 1. The Observed Effects of Mass Virtual Adoption on Job Performance, Work Satisfaction, and Collaboration / Carmine Gibaldi and Ryan T.W. McCreedy -- Chapter 2. Towards a Conceptual Model of Work from Home and Workplace Loneliness / Ada T. Cenkci -- Chapter 3. The Missing Spark of Digital Channels: Digitalisation and Informal Employee Voice Behaviour / Christina Fuchs and Astrid Reichel -- Chapter 4. The Life Integration Framework: Women's Global View on Work-Life and Work From Home / Kerri Cissna, Lene Martin, Margaret J. Weber, and Amanda S. Wickramasinghe -- Chapter 5. Working from Home: College Professors' Perspective / Holly Chiu, William Hampton-Sosa, and Tomas Lopez-Pumarejo -- Section II: Organizational Perspectives -- Chapter 6. Shared Leadership during the Covid-19 Crisis: A Case Study / Neha Chatwani -- Chapter 7. Leveraging the New Work From Home Normal to Promote Women's Success in Male-Dominated Fields / Seterra D. Burleson, Debra A. Major, and Kristen D. Eggler -- Chapter 8. Enhancing Work Engagement in Diverse Employees Via Autonomy: Acknowledging Introversion and Extroversion Workspace Preferences / Devalina Nag -- Chapter 9. Remote Work Implications for Organizational Culture / Sumita Raghuram -- Chapter 10. A Multilevel Perspective on Norm Formation and Organizational Culture during Times of Uncertainty / Matthew D. Deeg, Andrew Fitzgerald Henck, and Doreen Matthes -- Chapter 11. Agent-Scene Romanticization of WFH: Pentadic Criticism of WFH Representations in Popular Culture / Elizabeth Spradley and R. Tyler Spradley -- Chapter 12. Work from Home among Start-ups in India: An Institutional Logics Perspective / Anirudh Agrawal, Payal Kumar, Shalaka Sharad Shah, and Pawan Budhwar.
Includes index.
Print version record.
Keywords: elektronické knihy; electronic books; Telecommuting; Flexible work arrangements; Business & Economics -- Human Resources & Personnel Management; Working patterns & practices